Coping pain strategies, aggression and anxiety in professional martial arts athletes - Glinska-Wlaz, J.; Huzarska-Rynasiewicz, I.; Warzocha, T.; Grymanowski, J.; Wlaz, L. (Journal of Physical Education and Sport, 2025)
Introduction: Martial arts are associated with the ability to control one's emotions, to deal with opponents and the challenges of pain. They are often associated with physical contact with an opponent and various challenges as a result. Martial arts athletes can experience anxiety, pain and aggression in the terms of their sport their performance and in the context of the discipline. Problem Statement and Approach: The following research aims to examine the relationship between aggression, pain coping strategies and anxiety in athletes training in martial arts. Furthermore, the factors were tested in comparison with non-training individuals. Material and Methods: In the study a sample consisted of martial arts athletes (N=50) and non-training academic students (N=50). To measure the studied concept several questionnaires were used: the Pain Coping Strategies Questionnaire (CSQ); the Buss-Perry Aggression Questionnaire (BPQA); the State-Trait Anxiety Inventory (STAI). Results: The results showed that athletes present higher results in pain management skills than the group of students. In the case of the self-assessment of the trait and state relating to anxiety, the athletes` results were lower than in the student group. The results presented in the group of athletes a strong correlation in the anger and physical aggression relationship. In the group of students, the strongest correlation relationship was also shown for the anger and physical aggression relationship. Conclusions: Our results showed the relationship between psychological anxiety, pain management and aggression in martial arts athletes compared to non-training individuals. Athletes have lower levels of anxiety and also aggression compared to students. In both the athlete and control group, control of one's own arousal is positively related to distraction strategies. Knowing how athletes psychologically cope with difficult factors such as pain and anxiety can be valuable feedback for researchers and practitioners.